Social innovation assessment?: Reflections on the impacts of social innovation on society - outcomes of a systematic literature review = ¿Evaluación de la innovación social? : Reflexiones sobre los impactos de la innovación social en la sociedad - resultados de una revisión sistemática de la literatura - Mildenberger, Georg; Schimpf, Gudrun-Christine; Streicher, Jürgen (European Public & Social Innovation Review, 2020)
Today we face many societal problems, such as climate degradation, energy shortages, increasing inequality, and demographic change. Solutions for these problems require far-reaching changes and new and untried approaches. Social Innovation (SI) could be a significant factor in tackling the challenges to come. The ‘reflection on the long-term effects of social innovations’ is a relatively new topic but is attracting growing interest. While technology assessments are regularly used to study the consequences of technical innovations, similar assessments for social innovations are rare. This paper explores and analyses the current state of theoretical, conceptual work on the assessment for SI and their consequences, related concepts, and relevant activities. Perspectives and options for further developments in this field are derived. The method used is a structured literature review. The results show that scientific research concerning the assessment of the consequences of social innovations seems to be still in its infancy. The boundaries between established topics (such as sustainability, user orientation, including social entrepreneurship) and newer concepts are fluid. However, alongside the different approaches and views, a certain convergence of perspectives with regard to the consequences and effects of (social) innovations can be observed. Similar questions and issues are dealt with using similar approaches and methods, and are sometimes confronted with similar obstacles. - - Resumen - Hoy enfrentamos problemas sociales como la degradación ambiental, carencias energéticas, creciente desigualdad y cambio demográfico. Las soluciones para estos problemas requieren cambios profundos y enfoques nuevos. La Innovación Social (IS) podría ser un factor significativo para abordar los desafíos venideros. La “reflexión sobre los efectos a largo plazo de la innovación social" es un tema relativamente nuevo, pero suscita un interés creciente. Si bien las evaluaciones tecnológicas se utilizan regularmente para estudiar las consecuencias de las innovaciones técnicas, otro tipo de evaluaciones son raramente utilizadas. Este artículo explora y analiza el estado actual del trabajo teórico y conceptual sobre la evaluación de la IS y sus consecuencias, conceptos relacionados y actividades relevantes. También se obtienen perspectivas y opciones para futuros desarrollos en este campo. El método utilizado es la revisión de la literatura estructurada. Los resultados muestran que la investigación científica sobre la evaluación de las consecuencias de las innovaciones sociales parece estar todavía en sus inicios. Los límites entre los temas establecidos (la sostenibilidad, orientación al usuario, emprendimiento social) y los conceptos más nuevos son fluidos. Sin embargo, junto a los diferentes enfoques y visiones, se puede observar una cierta convergencia de perspectivas en cuanto a las consecuencias y efectos de las innovaciones (sociales). Las cuestiones y problemas similares se abordan utilizando enfoques y métodos similares y, a veces, se enfrentan a obstáculos similares. - Palabras clave: innovación social; revisión de literatura estructurada; impacto; evaluación; lado oscuro; reflexiones; consecuencias; medición. - - DOI: https://doi.org/10.31637/epsir.20-2.1
Gesehen am 16.11.2021